Analisis Pengaruh Beban Peralatan Bengkel Terhadap Intensitas Konsumsi Energi (IKE) di PT. Buana Jaya Lestari - Taufik Refyandra; Rahmaniar; Parlin Hambali (Jurnal Nasional Teknologi Komputer, 2025)
This study analyzes the Energy Consumption Intensity (ECI) at the multi-story motorcycle workshop of PT. Buana Jaya Lestari in Medan to identify energy consumption characteristics and optimization potential. The research method used energy audits, direct measurements, and historical energy consumption data analysis over a 12-month period. The research object is a multi-story workshop with a total area of 1,850 m² distributed across three floors with different functions. The results of the study show a total ECI of 100.67 kWh/m²/year, which meets the national standard for commercial buildings with partial air conditioning. Energy consumption distribution per floor varies significantly: floor 1 (138.09 kWh/m²/year), floor 2 (99.84 kWh/m²/year), and floor 3 (48.00 kWh/m²/year). The air conditioning system dominates energy consumption with a contribution of 42.1%, followed by the lighting system (23.9%), workshop equipment (20.0%), and support systems (14.0%). The most influential factors are external ambient temperature (correlation 0.85) and the number of vehicles served (correlation 0.78). Energy savings potential reaches 13.4% or 24,878 kWh/year through optimization of the air conditioning system and retrofitting of the lighting system. Implementing energy conservation strategies can result in financial savings of Rp 37,317,000/year, a reduction in CO₂ emissions of 17.41 tons CO₂eq/year, and a decrease in the Energy Performance Index (EPI) to 87.25 kWh/m²/year.